Microeconomic Resilience and Influence on Accounting Innovation With the Polythetic Cluster Modeling Techniques in the United States - Kasztelnik , Karina; Brown, Eric (Journal of Accounting and Finance, 2021)
Accounting innovation defines world economics ambition as the significant level for increasing growth through driving business efficiencies and releasing creativity. Also, accounting innovation shapes at the global, national, and local levels and become an autotelic value in the age of economic globalization. A novel research approach uses the first time in financial economics the polythetic cluster modeling techniques to present the findings. The machine learning model justified the accuracy compare to previous research studies. The findings can contribute to a better understanding of the impact of business resilience on the accounting innovation used by business experts and policymakers around the World. The research results represent a further step towards developing more machine learning models into a future research study to achieve more accuracy in the findings and discussions. The concurrent cluster methods research presented here confirms that the business artificial intelligence methods and the human domain knowledge interpretation may support the current microbusiness leadership to better understand their essential business decision as a major part of the modern business behavioral prescriptive analytics. Therefore, this research study needs to be of value to all business owners worldwide that wish to significantly improve their behavioral business data insight for business strategy management decisions every day.